Genome-wide identification reveals unprecedented expansion and stress-responsive expression patterns of the lipoxygenase gene family in soybean (Glycine max L.) - Lamlom, Sobhi F.; Zhang, Taifeng; Wang, Yanbo; Ren, Honglei; Song, Fuqiang; Feng, Guojun (Frontiers in Plant Science, 2025)
BackgroundLipoxygenases (LOXs) catalyze polyunsaturated fatty acid oxygenation and regulate plant stress responses and oxylipin biosynthesis. This study provides comprehensive genome-wide characterization of the soybean LOX gene family, revealing unprecedented expansion and functional diversification.MethodsWe identified unique GmLOX gene loci through systematic database searches and domain analysis, selecting representative isoforms to avoid transcript redundancy. Phylogenetic analysis compared 43 GmLOX with 6 AtLOX proteins. Protein structures, conserved domains, promoter cis-regulatory elements (2,000 bp upstream), and synteny relationships were characterized. Expression profiling under four abiotic stresses (alkaline, drought, heat, salt) across six time points (0–24 h) was performed using qRT-PCR.ResultsGenes distribute unevenly across 10 chromosomes, with highest densities on Gm10 (11 genes), Gm08 (9 genes), and Gm07 (8 genes). Phylogenetic analysis revealed six evolutionary clades with soybean-specific expansion. Structural analysis showed 92% encode full-length proteins (average 887 amino acids) with conserved PLAT/LH2 (97%) and catalytic domains. Promoter analysis identified 23 regulatory element categories, including hormone-responsive (auxin 97%, gibberellin 89%, ABA 94%), stress-responsive (95%), and light-responsive elements (100%). Synteny analysis demonstrated ancient whole-genome duplications and recent tandem duplications drove expansion. Expression profiling revealed five functional categories: alkaline-specific, drought-dominant, heat-specific, salt-responsive, and multi-stress responsive genes. GmLOX16 showed exceptional multi-stress responsiveness (40-fold salt, 38-fold alkaline), GmLOX13 displayed strongest heat response (20-fold), and GmLOX17 exhibited peak drought sensitivity (7-fold).ConclusionSoybean possesses the largest crop LOX family with remarkable functional diversification maintained under strong selective pressure (92% functional retention). Key stress-responsive genes, particularly GmLOX16 and GmLOX13, represent valuable targets for molecular breeding to enhance climate resilience, providing critical genetic resources for sustainable crop improvement.